1974
DOI: 10.1111/j.1752-1688.1974.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

MATHEMATICAL GENERALIZATION OF STREAM TEMPERATURE IN CENTRAL NEW ENGLAND1

Abstract: The empirical fit of an annual harmonic function to stream temperature measurements in central New England can be improved by considering a harmonic period of less than 365 days instead of 365 or 366 days. Generalized equations, developed using periodic temperature data from 27 streamflow stations, allow predictions of stream temperature at any site given (1) the mean basin altitude (E), in meters above mean sea level, and (2) station latitude (LAT), in degrees. Stream temperature t, in degrees Celsius, on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…It should be noted that Equation (6) needs to be modified when the sinusoidal function is fitted to a period shorter than one year (e.g., Tasker and Burns, 1974).…”
Section: Autoregressive Modelsmentioning
confidence: 99%
“…It should be noted that Equation (6) needs to be modified when the sinusoidal function is fitted to a period shorter than one year (e.g., Tasker and Burns, 1974).…”
Section: Autoregressive Modelsmentioning
confidence: 99%
“…. On peut utiliser différentes techniques de lissage ; les séries de Fourier utilisées depuis le XIX e siècle (Plantamour, 1863) et reprises par de nombreux auteurs (Ward, 1963 ;Tasker, 1974 ;Salas, 1980 ;Steele, 1982) dans cet article, contrairement à ce qui a été fait pour l'Étude Globale Rhône.…”
Section: Analyse Des Régimes Thermiques Du Rhône Et De Ses Principauxunclassified
“…Daily streamfiow data from U. S. Geological Survey gages were obtained for 1948 through 1993 for several major rivers that are tributary to the Upper Illinois Waterway. Table 1 been proposed (Cluis, 1972;Kothandaraman, 1974;Tasker and Burns, 1974;Smith, 1981;Krajewski et al, 1982;among others). Stefan and Preud'homme (1993) have shown that simple linear regression models can be constructed relating water temperature to air temperature:…”
Section: Riversmentioning
confidence: 99%
“…Many authors have used a sinusoidal model to represent the annual cycle of water temperatures (Cluis, 1972;Kothandaraman, 1974;Tasker and Burns, 1974; among others). The monthly linear regression river temperature model for the DuPage River was replaced with a sinusoidal model.…”
Section: Sensitivity Analysismentioning
confidence: 99%